An experimental study of the repeated trust game with incomplete information - Vital Anderhub; Werner Güth; Dirk Engelmann (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
In the trust game first player 1 decides between non-cooperation or trust in reciprocity and then, in the latter case, player 2 between exploiting player 1 or rewarding him. In our experiment, player 2 can be a notorically rewarding player (this type is implemented as a robot strategy) or a human participant who may decide opportunistically. To allow for reputation formation, this game is played repeatedly. Learning can be analysed since participants play successively several repeated games with changed partners. In our computerized experiment, participants can explicitly rely on mixed strategies which allows testing the qualitative and quantitative aspects of reputation equilibria also at an individual level.
urn:nbn:de:kobv:11-10046848
Keywords: 330